Hicret’in 15. yüzyılında islâm sanatları sergisi : islamda halı sanatı = On the occasion of the fifteenth centennial of hegira islamic arts exhibition : carpets in islam : İstanbul-Turkey. ([Ankara])
[10], 39, [6] s.